2014
DOI: 10.1097/ccm.0000000000000318
|View full text |Cite
|
Sign up to set email alerts
|

Early Administration of Hydrocortisone Replacement After the Advent of Septic Shock

Abstract: In patients receiving hydrocortisone for septic shock, early initiation of treatment was associated with improved survival. This treatment was also associated with attenuated stimulation of tumor necrosis factor-α.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
46
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 20 publications
8
46
1
Order By: Relevance
“…Of note, hydrocortisone had no effect on IL-10 level when it has been administered more than 6 hours before the endotoxin. These data were confirmed in a recent issue of the journal (37). The authors demonstrated that early or late initiation of hydrocortisone treatment induces different patterns of TNF-α production and impact the mortality rate.…”
Section: Discussionsupporting
confidence: 52%
“…Of note, hydrocortisone had no effect on IL-10 level when it has been administered more than 6 hours before the endotoxin. These data were confirmed in a recent issue of the journal (37). The authors demonstrated that early or late initiation of hydrocortisone treatment induces different patterns of TNF-α production and impact the mortality rate.…”
Section: Discussionsupporting
confidence: 52%
“…This finding suggests that we should apply corticosteroid once adrenal insufficiency is identified, not wait until irreversible hypotension has developed. In support of this notion, a recent study showed that early corticosteroid therapy improves survival in septic shock patients (12,13); 3) this study also supports the use of corticosteroid cocktail. Sepsis induces a group of corticosteroids which may work together.…”
Section: Implications For Corticosteroid Therapymentioning
confidence: 60%
“…Numerous efforts have been made but the results are inconclusive (8)(9)(10)(11). Nevertheless, the debate is still ongoing and recent studies show that early corticosteroid therapy may improve survival in septic shock patients (12,13) or in sicker septic shock patients (14,15).…”
mentioning
confidence: 97%
“…This may be important because a recent, small study suggests that administration of corticosteroids within nine hours of vasopressor initiation leads to improved outcomes [28]. Conversely, a much larger study by Casserly et al showed that adjunctive corticosteroids are associated with increased adjusted hospital mortality even when prescribed within eight hours of vasopressor initiation [3].…”
Section: Discussionmentioning
confidence: 99%